PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP KEMAMPUAN MENGKRITIK CERPEN SISWA KELAS XI MAN 4 MANDAILING NATAL - Ito, Edida Pinta; Parapat, Lili Herawati; Afifah, Nur (CV. Alfa Pustaka, 2023)
The formulation of the problem in this study is: is there any application of the jigsaw cooperative learning model to the ability to criticize short stories for class XI MAN 4 Mandailing Natal students? The goal to be achieved in this study is to prove whether there is an application of the jigsaw cooperative learning model to the ability to criticize short stories of class XI MAN 4 Mandailing Natal. controlled by using the product moment correlation formula. In the calculations that have been done, it is obtained that the price is rcount> rtable or 0.031773> 0.0301. So thus the author can conclude that there is an application of the jigsaw cooperative learning model to the ability to criticize short stories for class XI MAN 4 Mandailing Natal students.